Global social dynamics and Philosophy of modern education - Semenov, Andry; Семенов, Андрій (Східноєвропейський національний університет ім. Лесі Українки, 2016)
The essay is concerned with the currently central issues of the philosophy of contemporary education in the context of the analysis of global social dynamics and through the lens of modeling the appropriate complex socio- anthropic systems. The essay is focused on the philosophical aspects of education as well as on the conceptual issues with regard to the implementation of the formula of permanent education in modern trans-border hyper-dynamic world.
Глобальна соціальна динаміка і філософія сучасної освіти
Keywords: global social dynamic; social modeling; philosophy of education; hyper-dynamic; глобальна соціальна система; динамічність соціального моделювання; філософія освіти; гіпердинамічність